POSSIBILITIES OF USING NARROW-CLAWED CRAYFISH FOR BIOLOGICAL RECLAMATION OF ARTIFICIAL WATER BODIES IN BUKHARA REGION (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article examines the scientific and practical possibilities of using the narrow-clawed crayfish as a biological reclamation agent to improve the ecological condition of artificial water bodies in the Bukhara region, which are characterized by high mineralization and eutrophication. The role of crayfish as detritivores and polyphages in the decomposition and utilization of excess organic matter accumulated in water bodies is analyzed. The research has shown that the introduction of a P. leptodactylus population has a positive impact on improving water quality indicators, limits the excessive growth of aquatic vegetation, and enhances the overall stability of the ecosystem by creating favorable conditions for the development of benthic organisms.
Keywords: Biological reclamation, narrow-clawed crayfish, Pontastacus leptodactylus, eutrophication, detritivore, artificial water bodies, Bukhara region, water quality, ecosystem.